THE SAFETY IMPACTS OF INCREASING THE SPEED LIMIT TO 70 MPH IN THE STATE OF WISCONSIN - Brose, Kirsten L. (My University, 2016)
The U.S. Department of Transportation’s National Highway Traffic Safety Administration determined in May 2014 that the social and economic burden of vehicle crashes in 2010 cost the United States $836 billion dollars (1). Several factors play a role in this price tag, one of which is speed. The United States has undergone several significant nationwide modifications to speed limit restrictions throughout its history. These changes include the 1974 National Maximum Speed Law which mandated a top posted speed of 55 mph, the 1987 Surface Transportation and Uniform Relocation Act which allowed states to increase speeds to 65 mph and the 1995 National Highway System Designation Act which gave speed limit authority back to individual states. Today, only 7 states maintain a 65 mph speed limit (including Hawaii which has the nation’s lowest maximum speed limit at 60 mph). Some states increased posted highway speeds to as high as 80 mph, including Texas which now has posted speed limits as high as 85 mph. On May 20, 2015, Wisconsin became the last Midwestern state to increase posted speed limits on select Interstate highways to 70 mph. The first changes occurred on 14 select roadway segments across the state, and since then, several other segments of Interstate highway have been increased as well. The increase in speed limit has brought with it great concern that the higher speeds will correlate to more dangerous high speed driving, higher incident rates, greater fatalities on the roadway and an overall more dangerous driving environment. Through the application of two WisTransPortal web applications; the MV4000 crash database and the VSPOC (Volume, Speed and Occupancy) Traffic Detector database these concerns were evaluated by analyzing incidents, traveled speeds and roadway volumes. The posted speed limit increase occurred in mid-June of 2015 across the state of Wisconsin. Therefore, the analysis of this research focused on data from July through December of the calendar years 2005 to 2015. This allowed for 14 years of data prior to the increase in speed limit to be compared to the most recent one year of data post speed limit increase, maintaining the same monthly duration to allow for consistency. The research looked at comparing total incidents occurring on the 14 routes, as well as fatal incidents, alcohol related incidents and speed related incidents. The presumption that a 5 mph posted speed limit increase directly correlates to a 5 mph operating speed increase was also evaluated. This analysis was performed by randomly selecting eight days throughout the year and comparing the average operating speed before and after the June 2015 posted speed limit increase. Additionally the two datasets were combined to study incidents per thousand vehicles on the roadway. In the first five months after the posted speed increase to 70 mph, it was determined that the higher speed limit did not show a statistically significant increase in the total number of incidents occurring on the segments of roadway increased to 70 mph. Additionally, those routes showed an increase in operating speed of 1.5 mph, well below the posted speed limit increase of 5 mph. Incidents per thousand vehicles on the roadway was also statistically lower in 2015, when the posted speed was increased to 70 mph. As of January 1, 2016, it can be concluded that the increase in posted speed limit to 70 mph has not led to a greater number of crashes on the Interstate highways in the state of Wisconsin. Additionally, average operating speeds have increased by 1.5 mph, well below the 5 mph posted speed increase.